2004
DOI: 10.1080/13576500342000130
|View full text |Cite
|
Sign up to set email alerts
|

Gödel, Escher, and degree of handedness: Differences in interhemispheric interaction predict differences in understanding self‐reference

Abstract: Ramachandran (1995) theorised that the left hemisphere (LH) is specialised for making a single and consistent interpretation of the self and the world, whereas the right hemisphere (RH) is responsible for monitoring anomalies in reference to these interpretations. If the anomalous information reaches a threshold, it interacts with the LH to update these interpretations or beliefs. Because mixed handers may have greater degrees of interhemispheric interaction compared to strong handers, they may have a lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…This framework, in essence, suggests that the mixed-handed advantage in episodic memory may reflect a more general mixed-handed advantage in metacognitive ability to access source memory (e.g., Shimamura, 2002). This idea is admittedly speculative, but it receives support from recent papers indicating a mixed-handed advantage in metacognitive processing (Niebauer, 2004;Niebauer & Garvey, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…This framework, in essence, suggests that the mixed-handed advantage in episodic memory may reflect a more general mixed-handed advantage in metacognitive ability to access source memory (e.g., Shimamura, 2002). This idea is admittedly speculative, but it receives support from recent papers indicating a mixed-handed advantage in metacognitive processing (Niebauer, 2004;Niebauer & Garvey, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Understanding may be achieved by holding a single statement in the nucleus while related, referential cognitions are represented in summary format and experienced as the fringe. In the first two studies, Niebauer and Garvey (2004) found that mixed handers understood this conceptual description better than strong handers. This understanding may have been experienced as a sense of rightness.…”
Section: The Fringe Of Consciousness Metacognition and Updating Belmentioning
confidence: 96%
“…Individual differences in fringe experiences may help explain the results of Niebauer and Garvey (2004). The experience of understanding Gö delÕs Incompleteness Theorem or appreciating a selfreferential picture by M.C.…”
Section: The Fringe Of Consciousness Metacognition and Updating Belmentioning
confidence: 97%
See 2 more Smart Citations